Proton irradiation effect on SCDs - 杨彦佶 陆景彬 王于仨 陈勇 徐玉朋 崔苇苇 李炜 李正伟 李茂顺 刘晓艳 王娟 韩大炜 陈田祥 李承奎 霍嘉 胡渭 张艺 陆波 朱玥 马克岩 吴帝 刘琰 张子良 尹国和 王宇 (Chinese physics C, 2014)
The Low Energy X-ray Telescope is one of the main payloads on the Hard X-ray Modulation Telescope satellite. Swept charge devices （SCDs） are selected as detectors for the Low Energy X-ray Telescope. As SCDs are sensitive to proton irradiation, irradiation tests were carried out on the HI-13 accelerator at the China Institute of Atomic Energy. The beam energy was measured to be 10 MeV at the SCD. The proton fluence delivered to the SCD was 3×10^8protons/cm2 over two hours. By comparing the performance before and after irradiation, it is concluded that proton irradiation affects both the dark current and the charge transfer inefficiency of the SCD. The energy resolution of the proton-irradiated SCD is 212 eV@5.9 keV at -60℃, while it before irradiated is 134 eV. Moreover, better performance can be reached by lowering the operating temperature of the SCD in orbit.